Ficus septica burm. F. Leaves Ethanolic Extract Induces Apoptosis in 7,12-dimethylbenz[a]nthracene-induced Rat Liver Cancer Quatitavely - Septhea, Dita Brenna; Anindyajati, .; Darma, Andita Pra; Nurzijah, Ika; Nugroho, Agung Endro (Indonesian Research Gateway, 2011)
The chemopreventive effect ofÃÂ Ficus septica Burm. f. leaves ethanolic extract (FLEE) was studied in 7,12-dimethylbenz[a]nthracene (DMBA)-induced rat liver cancer. Rats were divided into 5 group, 5 rats (5 wk of age Sprague Dawley rat) in each group. Group 1 was control diet group, administered with 0,5% CMC-Na as vehicle. FLEE was administered 750 mg/kgBW and 1500 mg/kgBW starting 4 wk until 5 wk after DMBA administration at the first until fifth wk to group 2 and group 3. Group 4 was control extract group, administeredÃÂ with 750 mg/kgBW andÃÂ groupÃÂ 5ÃÂ wasÃÂ DMBAÃÂ group.ÃÂ DMBAÃÂ isÃÂ aÃÂ carcinogenÃÂ toÃÂ induceÃÂ liverÃÂ cancerÃÂ wasÃÂ also administered in DMBA control group and all animals were necropsied at 6 wk after DMBA administration. Activity of inducing apoptosis was detected using Double Staining method in 750 mg/kgBW FLEE group compared to control group but no in 1500 mg/kgBW FLEE group resulted in 100% dead. Apoptotic cells would have orange flourescence but normal cells would have green flourescence detected by flourescence microscope. To investigate the protein that involved in apoptotic mechanism, we studied p53 expression using Imunohistochemistry (IHC). There was no difference expression of p53 in both tested and control groups. Based on the results, FLEE has a potency as chemoprentive agent because its activity on inducing apoptosis in liverÃÂ cancerÃÂ withÃÂ p53-independentÃÂ pathway.ÃÂ TheÃÂ mechanismÃÂ ofÃÂ apoptosisÃÂ inductionÃÂ ofÃÂ this extract needs to be explored by observing the expression of related proteins. Key words: apoptosis, Ficus septica, liver cancer, p53 independent pathway